Root canal treatment of teeth with curved root canals - Olczak, Katarzyna (Journal of Stomatology, 2017)
Introduction. Endodontic treatment of curved root canals is usually difficult, time-consuming and associated with complications. In order to avoid failure, appropriate instrumentation and techniques are needed. In the course of treatment, it is necessary to properly shape and enlarge the coronal part of root canals. Instruments should be directly inserted into the canal in a straight line. Apical patency treatment should be applied and a glide path should be created before the final preparation of root canals. Aim of the study. To present cases of root canal treatment in teeth with curved root canals and to describe possible complications and methods for addressing more difficult problems occurring during preparation of curved root canals. Materials and methods. Cases of primary treatment and retreatment of root canals with a significant degree of curvature were examined. Results. Good results were obtained in all cases. Canals were formed according to their original morphology along the entire working length. Conclusions. Even canals which are significantly curved can be treated by adequate application of modern instrumentation with nickel-titanium files.